(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research explores the correlation between specific personality traits (e.g., extraversion, conscientiousness, openness to experience) and the leadership styles adopted by educational leaders. It aims to understand how individual personality characteristics influence decision-making, communication, and overall effectiveness in school settings.